Developing the investment budgeting through evaluation of investment projects - الحمداني بهاء حسين; عبد الحميد احمد رعد (Journal of Economics and Administrative Sciences, 2018)
The aim of the research is to determine the impact of evaluating the investment projects in the development and preparation of investment budgets prepared by the economic units, since the investment projects are of an important and vital nature of the economic units, because these projects include the length of time for preparation and implementation and the accompanying period of this risk and uncertainties as well as need To the many funds to complete the project , The process of evaluating the implemented projects, which have been prepared an investment budget previously will contribute to the extent of matching the estimated data with the actual results or deviations, which is a step to avoid these errors in future projects. For the project and its implementation will contribute to the improvement of its preparation), and has been applied research in the laboratory opening, one of the laboratories of the General Company for Sufism industry. The researcher reached a number of conclusions, the most important of which is that the investment projects prepared by the company were not evaluated later after the implementation of the project and the company’s lack of commitment to the model prepared by the Ministry of Planning to prepare investment projects, In the light of the conclusions, the researcher recommends the need to evaluate the investment projects after the investment budgeting and implementation of the project for the evaluation of the importance of avoiding future errors and improve budgeting, as well as on the company following the form prepared by the Ministry of planning for its role in rationalizing investment projects.